Penerapan Pembelajaran Berdiferensiasi untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas IV SDN 06 Cakranegara Tahun Pelajaran 2024/2025 - Yanti, Supi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to determine the improvement in students’ critical thinking skills following the implementation of differentiated learning in Grade IV at SDN 06 Cakranegara during the 2024/2025 academic year. The subjects of the study were 25 students from Class IV A of SDN 06 Cakranegara. This research employed Classroom Action Research (CAR), consisting of two cycles, each comprising the stages of planning, implementation, observation, and reflection. A qualitative descriptive method was used, with data collected through observations and open-ended tests. The results of the study indicate that the implementation of differentiated learning can enhance students’ critical thinking skills. The average student learning activity, based on observation results, increased from 71% in Cycle I to 85% in Cycle II. An improvement was also observed in the students’ critical thinking test scores, with the average rising from 63.6 in Cycle I to 80.2 in Cycle II. This study concludes that differentiated learning effectively improves students’ critical thinking skills.